THE EFFECT OF BRUXISM ON NATURAL TEETH AND PROSTHETIC RESTORATIONS- REVIEW - Alice-Arina Ciocan - Pendefunda; Magda Ecaterina Antohe; Petronela Bodnar; Oana Tanculescu; Alina Mihaela Apostu (Romanian Society of Oral Rehabilitation, 2023)
Purpose. Based on the results of existing research in the literature on bruxism and prosthetic treatment, an attempt was made to draw conclusions about the existence of a possible relationship between the two. Material and method A literature search was conducted for articles in Medline/PubMed and School Google for articles using the terms "bruxism, "prosthetic treatment", dental wear, and relevant studies were analyzed. Results. Bruxism is a parafunctional habit with a multifactorial etiology. The role of bruxism in the etiology of dental wear is unclear, not considered a major cause. There is no specific treatment to stop bruxism, including prosthetic treatment. The present review addresses the relationship between bruxism and prosthetic treatment, mainly the effect of bruxism on prosthetic restorations. Conclusions. Bruxism can be included among the risk factors that generate difficulties during oral, dental or prosthetic rehabilitations with support on natural teeth or implants. These difficulties are represented by a large number of cases of failure in rehabilitation therapy in patients with bruxism.